The Location of Energy Plantations in the Sowing Structure and Its Evaluation with Linear Programming - Csipkés, Margit; Nagy, Lajos (International Journal of Engineering and Management Sciences, 2018)
The research is examining traditional arable crops and woody plants on the basis of their marginal contribution. Calculations of income, expenditure and revenue were made on the grounds of sectoral technologies, which were the basis of the value of marginal contribution of the given sectors. As the linear programming model is quite comprehensive, we used this method for our calculations. To compile our model, we have gathered all the necessary information from farmers of the region of the Northern Great Plain. The missing data was completed from the databases of the Hungarian Central Statistical Office (KSH), Institute for Agricultural Economics Research and Information Technologies (AKII) and the Statistical Office of the European Communities (EUROSTAT). In some cases, we also used data of the Agricultural Administration Office and the Ministry of Agricultural and Rural Development. Our goal is to compile a 12-year production structure that suits for the characteristics of the region of the Northern Great Plain by achieving the maximum marginal contribution of a feature-farm.